East of Eden Movie Still - Warner Bros.:::Creator::::::::::::
Cathy/Kate Ames (Jo van Fleet) walking by Cal Trask (James Dean) in Warner Bros adaptation of John Steinbeck's novel. RESTRICTED USE Digital copy only. No hard copy.